Comprehensive Theoretical Studies on 11-MeV Proton Based Tc-99m Production - Kambali, Imam (Makara Journal of Science, 2017)
The shortage of nuclear-reactor-based Tc-99m supply has led to increased research on cyclotron-based Tc-99m production. In this paper, Tc-99m radionuclides produced by a 11-MeV proton cyclotron is theoretically discussed in terms of the optimum thickness of natMo, natMoO3, and enriched 100Mo targets; expected impurities; and radioactivity yields of several (p,2n), (p,n), and (p,γ) based nuclear reactions. The SRIM 2013 codes and TALYS 2014 codes are employed to calculate the range of 11-MeV proton beams in the Mo-based targets and the excitation functions of the selected nuclear reactions, respectively. The calculated results indicate that 94m,95m,96mTc radionuclides would give rise to radionuclide impurities at the end of irradiation for natMo targets, whereas no significant impurities were theoretically detected for the enriched 100Mo target. At the end of bombardment, nearly 42.18 GBq/µA.hr of Tc-99m radionuclide is predicted to result in the 11-MeV proton-irradiated 100Mo target.